SOCIAL EFFECT (STATUS) OF FAMILY ECONOMICS, LEARNING MOTIVATION, AND INTERPERSONAL COMMUNICATION ON LEARNING SELF-STUDY OF CHRISTIAN SATYA WACANA HIGH SCHOOL - Bulu, Elshinta; Permatasari, Carolina Lita; Ismanto, Bambang (Universitas Negeri Semarang, 2019)
This study aims to determine the effect of Social (status) Family Economy, Motivation to Learn, and Interpersonal Communication on the Learning Independence of Satya Wacana Christian High School students. The population in this study were all Satya Wacana Christian High School students with 450 students. The samples taken were 100 students. The method of data collection uses a questionnaire. The data analysis technique uses descriptive analysis method, classic assumption test, multiple linear regression analysis, and hypothesis testing using the SPSS 16.0 program. The results of the research that have been carried out explain that: (1) there is no significant influence between the social (status) of the family economy on learning independence as indicated by the results of the calculation of 1,447 t table 1.664 and the significance value of 0.151 0.05. (2) there is a positive and significant influence between motivation to learn and learning dynamics as indicated by the results of the calculation of thitung 2629 t table 1.664 and a significance value of 0.010 0.05. (3) there is a positive and significant influence between interpersonal communication and learning independence as indicated by the calculation results that t count 3.151 t table 1.664 and significance value of 0.002 0.05. (4) there are positive and significant social influences (status) of family economy, learning motivation, and interpersonal communication on learning independence as indicated by the calculation results where the value of F count is 16.956 F table 2.70 and a significance value of 0.000 0.05.